An observational study on risk factors for stroke in hospitalised patients of Tertiary Care Hospital, Tirupati - M. APARNA,; S. FIRDOSE BASHA,; M. HARIKA,; M. SRAVAN,; P. RIHANA BEGUM,; M. NIRANJAN BABU, (International Journal of Pharma and Bio Sciences, 2018)
The objectives of the study were to determine the epidemiological risk factors of stroke in hospitalized patients at Sri Venkateswara Institute of Medical Sciences (SVIMS) for identification of different age groups of patients who were suffering with stroke, analyse the sex distribution and diseased states as risk factors for stroke. The study was carried out in the ward of the Department of neurology at Sri Venkateswara Institute of Medical Sciences Hospital, Tirupati. This study was a Hospital based Observational study. The study was planned over a Period of six months. Inclusion criteria were inpatients with stroke in department of neurology ward and patients who gave their informed consent were included in the study. Exclusion criteria were pregnant women and lactating women and patients who did not agree to participate were in the study. A structured patient data collection form was used to collect the patient’s details like age, sex, family history, past medical history, smoking, alcoholism, tobacco chewing, drug of abuse, physical activity, drug therapy and other disease states etc. as risk factors for stroke. One hundred patients with diagnosis of stroke were selected. Out of 100 patients 67(67%) were males and 33(33%) females. Risk factors distribution was: smoking 34 (34%), alcohol consumption 28 (28%), tobacco chewing 31 (31%), hypertension 62 (62%), diabetes mellitus 29 (29%), CAD 12 (12%), hyperlipidaemia 4 (4%), seizures 3 (3%), atrial fibrillation 3 (3%), myocardial infarction 4 (4%), ischemic heart disease 1 (1%), rheumatic heart disease 3 (3%). The risk factors for stroke were includes hypertension, diabetes, coronary artery disease, smoking, tobacco chewing and alcohol consumption primarily. The stroke due to risk factors can be reduced but requires proper management and counseling of patients, regular use of medication and changes in lifestyle.